A cross-sectional study to determine the prevalence of obesity, overweight and weight awareness among the students of a private medical college in Khulna - Hasanat, Md Abul; Paroi, Silvia; Begum, Arifa; Salma, Umme; Yeasmin, Syeda Farzana (Mediscope, 2020)
Background: Medical education is stressful throughout the whole course. Due to the medical curriculum and the examination pattern leads to psychological stress. Stressful condition leads to irregularity in diet, frequent fast food consumption & lack of exercise, each being considered as an important risk factor leading to overweight and obesity. Hence, this study was undertaken to determine the prevalence of obesity, overweight and weight awareness among the medical students. Objectives: Determination of BMI status of undergraduate medical students to evaluate their weight awareness, prevalence of overweight and obesity and also find out the relationship of the following risk factors with obesity & overweight; i) Opinion about self-image, ii) Physical activity and iii) Frequency of fast food consumption. Methods: A descriptive cross sectional study was conducted on 131 preclinical medical students of Ad-din Akij Medical College, Khulna from January 2018 to April 2018. Height and weight of 131 preclinical students were measured and Body Mass Index was calculated and categorized according to WHO criteria. Results: Out of 131 students 62% come under normal weight category, 21% come under overweight category, 10% come under obese category and 7% come under underweight category. Conclusion: Overweight is a rising problem among the medical students. Sedentary life style and frequency of fast food consumption was high among the overweight and obese students. This study itself created awareness about their weight and promote physical activity among the medical students. Mediscope Vol. 7, No. 2: July 2020, Page 103-107